Ekstrak Lidah Buaya (Aloe Vera) Menurunan Kadar Glukosa Darah Tikus Putih (Rattus Norvegicus) Yang Diinduksi Streptozotocin - Marzel, Rivaldi; Darwis, Iswandi; Windarti, Indri (Medula, 2023)
Diabetes mellitus (DM) is a chronic disorder in the metabolism of protein, fat and carbohydrates. Diabetes mellitus is described as an increase in blood glucose. DM cases in Indonesia rapidly increases. Diabetes mellitus  is a disease that requires anti-diabetes drugs continuously. Continuous use will have side effects that  encourages patients to look for alternative treatments that are cheaper, efficacious, without side effects, and easy to obtain such as herbal medicines. Many medicinal plants around the world contain antihyperglycemic compounds, such as Aloe vera.This is study experimental study using a randomized controlled design method with Post-test only Control Group Design. There were 24 rats consist of 4 treatment groups (K1, K2, K3, K4). (K1) = rats  were given by a standard diet. K2 = rats induced streptozotocin 40 mg/kgBW.K3 = rats were treated with metformin. K4 = rats were treated with Aloe vera extract 250 mg/kg BW. After 21st day,  blood glucose levels were measured. The research was conducted at the animal house of the Faculty of Medicine, University of Lampung. Samples were analyzed using the one way Annova test. Blood glucose levels of the 4 treatment groups were K1 = 67.16 mg/dl, K2 = 366.33 mg/ dl, K3 = 77.83 mg/dl, K4 = 127.16 mg /dl. The blood glucose level in the control and treatment groups were significantly different (p<0,05).  Aloe vera extract ameliorates blood glucose levels of streptozotocin-induced diabetes in white rats (Rattus norvegicus).